COLOR IS OUR ADORNMENT: रंग हमारा अलंकरण - Modi, Parvati (International Journal of Research -GRANTHAALAYAH, 2014)
Just as nature spreads color in its premises and makes it enchanting, in the same way we can make the atmosphere cheerful by combining colors. The effect of color is universal and one of our important happiness lies in the fact that we color With what abilities do we use it beautifully. Colors have a close relationship with human life. Every beautiful thing affects a man's heart and emotions. Pictures, textiles and houses related to different colors suit and excite the man. The beautiful colorful six-color reflection of nature is presented in front of us in its new form, which makes us enchanted. The beauty of each item depends on the proper combination of colors and the beautiful decoration. To decorate oneself, to make the picture attractive and to decorate the house, the choice of special colors has to be made by looking at the conditions, atmosphere, shape, form and use of the time. प्रकृति जिस प्रकार अपने प्रांगण में रंग बिखेर कर उसे मन-मोहक बना देती है, उसी प्रकार हम भी रंगों का संयोजन कर वातावरण को उल्लासपूर्ण बना सकते हैं।रंग का प्रभाव सार्वभौमिक है और हमारी एक महत्वपूर्ण खुषी इस बात में निहित है कि हम रंग का संुदरतापूर्ण उपयोग किस योग्यता से करते हैं।रंगों का मानव-जीवन से घनिष्ठ संबंध है। प्रत्येक संुदर वस्तु मनुष्य के हृदयों और भावनाओं को प्रभावित करती है। उपयुक्त विभिन्न रंगों से संबंधित चित्र, वस्त्र तथा घर मनुष्य को उत्साहित और आनंदित करते हैं। प्रकृति की सुदंर रंगीन छटा प्रतिक्षण हमारे सन्मुख नया रूप धारण कर प्रस्तुत रहती है, जिससे हम मुग्ध हो जाते हैं। प्रत्येक वस्तु की संुदरता रंगों के उचित मेल एवं सुंदर ढंग से सजाने पर निर्भर करती है। अपने को सुसज्जित करने, चित्र को आकर्षक बनाने तथा घर को सजाने में विषेष रंगों का चुनाव, उस समय की परिस्थिति, वातावरण, आकार, रूप तथा उसका उपयोग देखकर करना पड़ता है।